Solve this equation: -7x + 12 – 2x = 23 + 13.0
Step 1: Simplify by combining like terms that are on the
same side of the equation. Which terms can be
combined?

Respuesta :

Answer:

Step-by-step explanation:

We can combine the -7x and the -2x and the left side to get -9x and the 23 and 13 on the right side to get 36.

This gives us

-9x + 12 = 36

Subtacting 12 from both sides gives us

-9x = 24

dividing by -9 gives us

x = - 8/3

Answer:

see below

Step-by-step explanation:

-7x + 12 – 2x = 23 + 13.0

Combine like terms

(-7x-2x) +12 = (23+13)

-9x +12 = 36

Subtract 12 from each side

-9x +12 -12 = 36 -12

-9x = 24

Divide each side by -9

-9x/-9 = 24/-9

x = -8/3

ACCESS MORE